Sawing toward the fibular head during open-wedge high tibial osteotomy carries the risk of popliteal artery injury. - Kang, Taehoon; Lee, Do Weon; Park, Jae Young; Han, Hyuk-Soo; Lee, Myung Chul; Ro, Du Hyun (Knee Surgery, Sports Traumatology, Arthroscopy, 2020)
Purpose: Popliteal artery injury is a rare but devastating complication of open-wedge high tibial osteotomy (OWHTO). The objectives of this study were: to document the location of the artery in the virtual osteotomy plane (VOP), to measure the minimal distance between the popliteal artery and three virtual saw-progression lines (VSLs), and to present a safe sawing technique for OWHTO.Method: In total, 45 computed tomography angiographies were reconstructed and virtual osteotomy was simulated using 3D image-processing software. The VOP was defined as an inclined plane commencing 3.5 cm below the articular plane towards the fibular head. VSLs were defined as saw-progression guidelines that lie on the VOP: "VSL-mid" runs from the midpoint of the tibial medial cortex towards the fibular head; "VSL-ant" starts from the same point as VSL-mid, but runs 10° anterior to the fibular head; and "VSL-post" runs 10° posterior to the fibular head. The distances between the popliteal artery and the three VSLs were measured, and the risk of injury was assessed.Results: The popliteal artery was located 20.7° posterior to VSL-mid and 51 mm from the starting point. The minimum distance between the popliteal artery and VSL-mid was 18 mm (99% confidence interval 9-27 mm). When the saw was moved along VSL-mid, 42% of the arteries were susceptible to injury. However, when it followed VSL-ant, there was no risk of injury.Conclusions: Sawing toward the fibular head carries a risk of popliteal artery injury and should not be performed. When sawing in OWHTO, the recommended target should be 10° anterior to the fibular head. This technique eliminates the risk of popliteal artery injury.